Paráfrase : uma questão de discurso e de sujeito - Santos, Ruth Léa (2008)
This research investigated the paraphrase as an argumentative activity that differs from the point of view of the classical conception, which sees it as an attempt to a simple translation/reproduction of a same context, expressed in different words. In our conception, the paraphrase is, characteristically, a reformulating strategy, where the subject/author intentionally retakes a statement from a different communicative context, causing a displacement of meaning in which the paraphrase takes over an important role in the argumentative activity of the text. These shifts in meaning occur even in situations in which the paraphrase is contingent, as in the selected corpus for this work, i. e. essays from the university entrance examination, in which a selection of texts is presented as the base to the structuring of the text. So, a comprehension of the argumentativity caused by the paraphrase was researched. The central inquiry in this paper is: What’s the effective participation of the subject/author in paraphrastic when building a textual structure for the construction/production of meaning? In other words, which meaning displacement is triggered by the paraphrase in the argumentative process? As a methodological strategy, with the purpose of highlighting the role that the paraphrase takes over in the discourse/text, we used the paraphrase categories postulated by Ribeiro (2001), modeling, intensifying or emphatic, gradual, referential, explanatory, exemplifying, eliciting. The results led us to defend that the paraphrase is argumentatively produced according to the subject/author’s speech project which, by taking the ‘already said’ and saying it in other way, adds new meanings to the text.